What is radio good for? Strategic roles for the medium - Ingram, Andrew (Henry Stewart Talks, 2008)
Radio is well-known for being a tactically useful medium, What role can it play in a strategic media plan?, Latest research into communications effectiveness, identifying the true strengths of the medium, High level of trust and very low levels of ad avoidance
Archived at 2022/03/17